Total asymmetric syntheses of iminosugars - Figuccia, A; Aude Figuccia (2015)
This thesis is concerned with the development of ring-closing iodoamination and ringexpansion methodology and its subsequent application to the asymmetric syntheses of pyrrolidine and piperidine iminosugars. Chapter 1 highlights the remarkable biological properties displayed by iminosugars and introduces methods for the formation of the pyrrolidine and piperidine sub-classes. Chapter 2 describes investigations into the ring-closing iodoamination of bishomoallylic amines which occurs with concomitant N-debenzylation to give an iodomethyl pyrrolidine scaffold. Conversion to the corresponding aziridinium species followed by its regioselective intermolecular ring-opening by H2O enabled the synthesis of (+)-2,5-dideoxy-2,5-imino-Dglucitol (DGDP). A protocol for the preparation of its 1-deoxy-1-amino analogue (+)-ADGDP was also developed. Chapter 3 details studies into the ring-expansion of iodomethyl pyrrolidine scaffolds via the trapping of CO2 (from NaHCO3) to produce cyclic carbonates as single diastereoisomers. Subsequent deprotection of these piperidines allowed the syntheses of (−)-1-deoxymannojirimycin (DMJ) and (+)-1-deoxyallonojirimycin (DANJ) to be completed. Chapter 4 delineates investigations into the trapping of alternative “X=C=Y” electrophiles, via the ring-expansion methodology developed in Chapter 3, initially utilising a model system. These studies culminated in the development of the trapping of p-TsNCO and the application of this methodology in the total asymmetric syntheses of (−)-ADMJ and (+)-ADANJ, the 2-deoxy-2-amino analogues of (−)-DMJ and (+)-DANJ, respectively. Chapter 5 contains full experimental procedures and characterisation data for all compounds synthesised in Chapters 2, 3 and 4.